Dating Methods of Pleistocene Deposits and Their Problems: I. Thermoluminescence Dating - Dreimanis, Aleksis; Hutt, Galina; Raukas, Anto; Whippey, Patrick (Geoscience Canada, 1978)
Summary Thermoluminescence (TL), is nowwide-ly used in archeology for the absolute dating of ancient pottery. During the last decade, particularly in the USSR, it has also been applied with mixed success to the dating of Pleistocene loess, buried soils, glaciofluvial, glaciolacustrine and marine deposits, and even tills. The purpose of this paper is to stimulate investigation of the application of this method to geological problems. Absolute dating methods beyond the radiocarbon dating range are urgently needed, particularly in the Pleistocene stratigraphy of North America. Therefore, even those relative or semi-absolute dating methods which have the potential eventually to provide reliable absolute dates, have to be investigated. The TL dating method belongs to this category, with its dates ranging between 103 and 10^ years B.P. Major problems to be investigated concern the fact that Pleistocene sediments do not always have a well established zero point for TL, and post-depositional changes may also have a profound effect on the TL. Quartz is one of the most suitable materials for TL dating known so far, and its use has been investigated recently at the Institute of Geology in Tallin. The best results have been obtained by using quartz grains 100-140 ìéç in size, after their outer layer has been removed by HF to exclude the TL caused by « -radiation.